Perception and Motivation Analysis of Purchase Decisions in Lumajang - Samsuranto Samsuranto (Jurnal Ilmu Manajemen Advantage, 2021)
This research is a type of quantitative research by looking for the relationship between the independent variable and the dependent variable. The purpose of this study is to prove that consumer perceptions and consumer motivation partially or simultaneously influence purchasing decisions at Graha Mulia Plaza Lumajang. The sample used in this study was 75 respondents. The sampling method was non-probability sampling with incidental sampling technique. This study uses multiple linear regression analysis techniques. The results of this study indicate that partially consumer perceptions have no significant effect on purchasing decisions and consumer motivation has a significant effect on purchasing decisions. Meanwhile, simultaneously, the variables of consumer perception and motivation have a significant effect on purchasing decisions at Graha Mulia Plaza Lumajang. The results of the coefficient of determination show that 47.1% of purchasing decisions can be explained by variables of consumer perception and consumer motivation, while the remaining 52.9% of purchasing decision variables are influenced by other variables not examined in this study.